Characterizing the rod pathway in cone-dominant thirteen-lined ground squirrels - Ferguson, Riley; Miyagishima, Kiyoharu J.; Nadal-Nicolas, Francisco M.; Li, Wei (Frontiers in Ophthalmology, 2023)
AII-amacrine cells (AIIs) are widely accepted as a critical element of scotopic pathways mediating night vision in the mammalian retina and have been well-characterized in rod-dominant mice, rabbits, and non-human primates. The rod pathway is characteristic of all mammalian eyes, however, the anatomic and physiologic role of AIIs and the rod pathways in cone dominant thirteen-lined ground squirrels (TLGS) is limited. Here, we employed both immunohistochemistry and electrophysiological approaches to investigate the morphology of AIIs and functional aspects of the rod pathway in TLGS. In all TLGS retinas examined, putative AIIs were calretinin-positive and exhibited connections to rod bipolar cells with decreased cell density and expanded arborization. Notably, AIIs retained connections with each other via gap junctions labeled with Connexin36. Comparisons between single photoreceptor recordings and full-field electroretinograms revealed scotopic ERG responses were mediated by both rods and cones. Thus, the components of the rod pathway are conserved in TLGS and rod signals traverse the retina in these cone-dominant animals. AIIs are sparsely populated, matching the diminished rod and rod bipolar cell populations compared to rod-dominant species. The infrequent distribution and lateral spacing of AII’s indicate that they probably do not play a significant role in cone signaling pathways that encode information at a finer spatial scale. This contrasts with the mouse retina, where they significantly contribute to cone signaling pathways. Therefore, the AII’s original function is likely that of a ‘rod’ amacrine cell, and its role in cone pathways in the mouse retina might be an adaptive feature stemming from its rod dominance.